Cyclic behavior of seismically non-conforming interior reinforced concrete beam–column joints - Sabbahfar, Peyman (2025)
The cyclic behavior of reinforced concrete (RC) beam–column joints (BCJs) is still one of the critical issues in structural engineering. In this context, for the purpose of gaining a more in-depth insight about the sophisticated behavior of BCJs under cyclic loading scenarios, the current work aims to investigate the cyclic behavior of reinforced concrete beam–column joints. The cyclic behavior of four interior reinforced concrete beam–column joints, with plain and deformed bars, which are representative of the seismically nonconforming structures from the 1970s, were experimentally investigated. The corresponding results of the specimens were compared with each other to better understand and highlight the differences between the force–drift curves and envelopes and damage patterns of each of the specimens. Furthermore, a numerical validation of the laboratory testing results was established with the DIANA FEA code for both monotonic and cyclic loading scenarios, and the force–displacement plots were compared with the associated laboratory results for validation purposes. The crack propagation and final damage states of the numerical models of beam–column joints are presented and discussed in detail. The results showed good agreement between the numerical and experimental behavior, and a graphical representation of the critical regions affected by damages was also shown, which could ultimately contribute to future retrofitting solutions for strengthening the BCJ region in existing RC structures.